An In-Service Teacher Training Model as a Basis for an Effective Integration of ICT in Education in Morocco - Lmortaji, Hajar (Journal of Information Systems and Technology Management, 2024)
This article presents a descriptive study of the in-service Teacher training program that aims at integrating ICT in the Moroccan education system, which is one of the missions of the GENIE program - Generalization of Information and Communication Technologies in Education, led by the Moroccan Ministry of National Education, Preschool and Sports. The main objective of this work is to assess the in-service teachers training and highlight its contribution in the process of integrating ICT in the Moroccan education system, as well as the limitations and challenges of its implementation in the absence of any reliable and outstanding benchmarks. The study is conducted within a mixed approach for the data collection based on a survey, a focus group and a documents analysis.